Dysfunctional eating attitudes and behaviors among French elite athletes: the impact of psychological characteristics and the sporting calendar - Daubresse, Amandine; Meignie, Alice; Antero, Juliana; Hanon, Christine; Mériaux-Scoffier, Stéphanie (Frontiers in Psychology, 2024)
Background Research on sport psychology suggests that athletes are at risk of developing dysfunctional eating attitudes and behaviors (DEAB), however the origins of these behaviors remain largely unexplored. The present study aims to identify factors (i.e., personality traits, anxiety levels, eating attitudes and behaviors, the internalization of sport thinness norms, and resilience) associated with the development of DEAB among female endurance athletes, in training and competition. Method A longitudinal follow-up study was conducted among 14 elite female athletes who were tested daily, weekly, and quarterly over 12 months in 2022, for a total of 545 measures. Participants completed questionnaires assessing personality traits, anxiety levels, eating attitudes and behaviors, the internalization of sport thinness norms, and resilience. Descriptive statistics were calculated for all study data, and odds ratios were conducted to compare the variance of psychological factors and sporting factors depending on the level of DEAB and the sport period. Significance was set at p < 0.05. Results Overall, 28% of our sample of athletes were identified with DEAB. Among those with DEAB, scores for agreeableness, anxiety, and competitive anxiety were significantly higher, while scores for resilience were significantly lower than those without DEAB. During the competitive season, scores for self-regulatory eating attitudes and the internalization of thinness norms were significantly higher than during the training period. Conclusion Our results suggest a greater probability of DEAB among athletes who exhibit the trait of agreeableness, experience anxiety during competition, and lack resilience. The competitive season was also identified as a period conducive for developing DEAB compared with the training period. Based on these results our study suggests preventive measures that can be implemented with athletes displaying these traits, with a particular emphasis during the competitive phase.